ROOTING OF QUBAHAN SCHOOL AN ANALYTICAL STUDY TO ARCHITECTURAL ITEMS (SPATIAL CONFIGURATION AND FORMALITY ELEMENT OF INTERIOR FACADES OF QUBAHAN SCHOOL) - AL-NUMMAN, RAEED S. AHMED (Journal of Duhok University, 2017)
In recent years, trends have emerged focusing on exploration  the architectural identity through  the study of the  domestic architecture properties, as a result appeared a large number of architectural studies that have targeted the  crystallize the privacy of every society. The most striking feature in the Kurdistan architecture are the buildings that express  cultural identity of the Kurdish community, also they are basis upon which the architectural identity, which represented the cultural identity to the Kurdish community, in various fields (social, cultural, political, historical, humanitarian, immigration and defensive tactics and Immunization). All of these elements and others represented the cultural identity of the Kurdish society and reflected directly on the architectural identity of the community, the pattern of local architecture in Kurdistan region is real reflection of the nature of the society. Culture and level of economic and social status, therefore architecture formed an original   part of the cultural identity as a responsive basic need of society and the nature of the living conditions. The lack of attention to local architectural character of the mountains regions, led to the appear   buildings do not belong to the identity of the local architecture, and due to the lack of research for local architecture Characteristics, it will study the architectural style (the principles form of traditional face) in ancient amadiyah city buildings, and the design characteristics of its buildings, so that architects benefit from it in modern buildings design.